2022
DOI: 10.1021/acs.orglett.2c00444
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (−)-3-Oxoisotaxodione

Abstract: The first total synthesis of the abietaquinone methide diterpenoid (−)-3-oxoisotaxodione is reported. The key enabling step is the use of a chiral bicyclic hydrazide as an organocatalyst for the enantioselective polyene cyclization of a (Z)-polyene substrate to form the cis-decalin core of the natural product. The α-oxo-paraquinone methide unit is formed by a two-step oxidation from a phenol, enabling an efficient synthesis of the natural product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Notably, 1 contains a cis fusion between their A and B rings, not usually encountered in the abietane family. Previously, only one naturally occurring cis -A/B fused abietane diterpenoid, 3-oxoisotaxodione, was known to feature this structural moiety, and it was further synthesized by enantioselective polyene cyclization to form the cis -decane core of the natural product. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, 1 contains a cis fusion between their A and B rings, not usually encountered in the abietane family. Previously, only one naturally occurring cis -A/B fused abietane diterpenoid, 3-oxoisotaxodione, was known to feature this structural moiety, and it was further synthesized by enantioselective polyene cyclization to form the cis -decane core of the natural product. , …”
Section: Resultsmentioning
confidence: 99%
“…Previously, only one naturally occurring cis-A/B fused abietane diterpenoid, 3-oxoisotaxodione, was known to feature this structural moiety, and it was further synthesized by enantioselective polyene cyclization to form the cis-decane core of the natural product. 22,23 Biological studies revealed that 1 and 2 showed significant antiplatelet activity induced by arachidonic acid (AA) with IC 50 values of 6.51 and 2.99 μM, which were approximately 20 and 40-fold better than the positive control aspirin (IC 50 : 129.05 μM), respectively (Table 2 and Figure S3). Additionally, a lactate dehydrogenase (LDH) assay was used to estimate the platelet cytotoxicity of 1 and 2.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Additionally, substrate 1u with a ( Z )-1,4-enallene moiety was also tested under the standard conditions, and an inseparable mixture of 2a and 2u was obtained in 50% total yield and 1 : 1 diasteromeric ratio ( trans / cis ). 12,4 h ,5 e …”
Section: Resultsmentioning
confidence: 99%
“…30,31 In particular, we demonstrated that bicyclic hydrazide catalyst 1 (Scheme 1) efficiently catalyzed the bicyclization of (Z)-polyene substrates with high er's, enabling the synthesis of cis-decalin containing natural products. 32,33 The enantioselectivity of catalyst 1 arose from a fortuitous O-H-C interaction which stabilized the incipient charge as it developed in the polyene system and thus mimicked the ability of an enzyme to not only initiate cyclization but also to stabilize cationic intermediates and/or transition states along the pathway. However, poor selectivity was obtained in the cyclization of (E)-polyene substrates due to the possibility of multiple C-H-O interactions in the diastereomeric transition states.…”
mentioning
confidence: 99%